SaaS Cloud Security : Attacks and Proposedsolutions - Soufiane, Sail; Halima, Bouden (Transactions on Engineering and Computing Sciences, 2017)
Nowadays the Cloud has started to gain ground even in SMEs, in spite of that the Cloud is still unknown for several ... for others few reliable. SaaS represents a promising technology, which grows each year rapidly. Only at the security level, there are many obstacles, and becomes a major problem against its adoption. For example the public cloud represents a huge risk since the data of several companies are stored at the same place, close to each other. For this reason the security of transiting or stored data in the SaaS remains a challenge for providers in order to gain the confidence of the customers. SaaS remains the target of several attacks, such as network attacks, etc., which aim to disrupt its operation. Therefore, it is essential to deal with these attacks, and tried to minimize vulnerability and adopt new security concepts. Through this document, we are going to study the security of SaaS, We will try to find the burly and feeble points of the most famous clouds such as Google Amazon, Microsoft, and come out with Countermeasures and proposals solution.